(untitled) - Larcher, W. (New York, 1983)
Contents: The environment of plants; radiation and temperature; carbon utilization and dry matter production;the utilization and cycling of mineral elements.
Thâm cứu sinh lý và sinh thái cây trồng
Keywords: Plant ecology,Sinh thái thực vật